2021
DOI: 10.1155/2021/6211609
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effects of Chinese Materia Medica Processing on the Hypoglycemic Activity and Chemical Composition of Anemarrhenae Rhizoma

Abstract: Purpose. To compare the hypoglycemic effects of different extracts of Anemarrhenae Rhizoma (AR) before and after being stir-baked with salt water on the diabetic mice and to detect the contents of 8 components in the corresponding active parts simultaneously using the UPLC-MS method, in order to screen the better extracts for diabetes and to clear the material basis for enhancing hypoglycemic activity of Anemarrhenae Rhizoma stir-baked with salt water (SAR). Methods. Taking spontaneous type II diabetic db/db m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In addition, previous research found that salt processing significantly improved the hypoglycemic effect of AR. 8,9 The strengthening effect of salt-processed Anemarrhenae Rhizoma (SAR) is consistent with the traditional Chinese medicine theory of “yin deficiency-engendered heat dry” in the pathogenesis of diabetes. 10 The synergistic mechanism of AR after salt processing is shown in Fig.…”
Section: Introductionsupporting
confidence: 60%
“…In addition, previous research found that salt processing significantly improved the hypoglycemic effect of AR. 8,9 The strengthening effect of salt-processed Anemarrhenae Rhizoma (SAR) is consistent with the traditional Chinese medicine theory of “yin deficiency-engendered heat dry” in the pathogenesis of diabetes. 10 The synergistic mechanism of AR after salt processing is shown in Fig.…”
Section: Introductionsupporting
confidence: 60%
“…Semen Alpiniae Katsumadai 9 g Stomachic, antiemetic, inhibition of tumor formation, antioxidant, anti-inflammatory and antibacterial [36] Houpo Magnoliae Officinalis Cortex 9 g ntibacterial, anti-tumor, analgesic, anti-inflammatory and antioxidative effects [37] Xiangfu Cyperus rotundus L 9 g Antioxidant, anti-allergic, antipyretic, anti-inflammatory, antiemetic, hepatoprotective, anti-diarrhea, anti-malarial, neuroprotective, [38] and so on. "Wen li" medicine Wuyao Lindera aggregata 10 g Anti-hyperlipidemic, anti-tumor, anti-inflammatory, analgesic, and anti-oxidant [39] Yizhiren Alpinia oxyphylla Miq 12 g Ameliorating cognitive disorders and alleviating pathological brain injuries characteristic of neurodegenerative disorders [40] "Xingqi Zhitong" medicine Chuanlianzi Toosendan Fructus 12 g Anti-tumor, anti-inflammatory, analgesic, antiviral, anti-oxidative, insecticidal, antifeedant and other properties [41] Foshou Citri sarcodactylis Fructus 9 g Analgesic, anti-inflammatory, antidepressant [42] "Yangyin Shengjin" medicine Zhimu Anemarrhenae rhizoma 12 g Anti-inflammatory, antioxidant, antipyretic, antidepressant [43]…”
Section: Caodoukoumentioning
confidence: 99%
“…This plant belongs to the genus Anemarrhenae in the Liliaceae family, and the dried rhizome of this plant is used to make medicine. It has a bitter taste, which reduces fire and heat while nourishing yin and strengthening yang [4]. The primary components of Zhimu, ginsenosides and sapogenins, have anticoagulant, antioxidant, antibacterial, and anticancer properties.…”
Section: Introductionmentioning
confidence: 99%